IECON 2014 - 40th Annual Conference of the IEEE Industrial Electronics Society 2014
DOI: 10.1109/iecon.2014.7049083
|View full text |Cite
|
Sign up to set email alerts
|

Implementation analysis of GPRS communication for precision agriculture

Abstract: The implementation of precision agriculture relies on the acquisition of large amounts of spatially distributed data from a remote area. Specifically closed-loop irrigation systems requires the installation of a large group of sensor nodes distributed over a crop area, in order to measure soil moisture and climatic variables. Wireless sensor network (WSN) based on Zigbee protocol represents a popular communication solution for precision agriculture applications. However due the short range of Zigbee based node… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In the last few years, significant research is carried out on smart irrigation. In Salas et al (2014) , the authors suggested the implementation of general packet radio service (GPRS) communication as a gateway between wireless sensor network (WSN) and the Internet. Numerous data transmission techniques have been applied in closed-loop watering systems.…”
Section: Related Workmentioning
confidence: 99%
“…In the last few years, significant research is carried out on smart irrigation. In Salas et al (2014) , the authors suggested the implementation of general packet radio service (GPRS) communication as a gateway between wireless sensor network (WSN) and the Internet. Numerous data transmission techniques have been applied in closed-loop watering systems.…”
Section: Related Workmentioning
confidence: 99%
“…These two features are greatly determined by the communication networks employed in device developments. Previous literature has presented works using traditional communication networks, such as General Packet Radio Service (GPRS) cellular networks [ 27 , 28 ]. These networks are distinguished by their large deployment, which virtually guarantees their availability but presents a clear problem with battery consumption [ 29 ].…”
Section: State Of the Artmentioning
confidence: 99%